2011
DOI: 10.2134/agronj2011.0154
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Nitrogen Utilization and Grain Technological Quality in Durum Wheat: II. Grain Yield and Qualities

Abstract: Th e relationships between grain quality and N utilization in durum wheat (Triticum durum Desf.) have not been very thoroughly investigated. Th e aim of this study was to evaluate the eff ects of N fertilizer rate and water regime on grain yield and quality under Mediterranean conditions in relation to N utilization. Four durum wheat cultivars (Appio, Creso, Ofanto, and Simeto) were grown in fi eld trials under two water regimes (irrigated and rainfed) at three N levels (0, 60, and 120 kg ha -1 ) in southern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
7
34
0
Order By: Relevance
“…The observed protein levels were in line with those previously reported for old and modern durum wheat varieties cropped under low N input management (Quaranta et al, 2010;De Vita et al, 2007b) and were also comparable with those obtained at higher nitrogen rates by Giuliani et al (2011). The protein accumulation was shown to be highly dependent on genotype, soil fertility (available N) and environmental conditions (temperature, water) (Giuliani et al, 2011;Dupont et al, 2006). In our study, the growing season was observed to have a big effect on protein content, with a significant increase from 143.5 to 161.4 g/kg during the second year compared to the previous one.…”
Section: Macronutrient Profilesupporting
confidence: 91%
See 2 more Smart Citations
“…The observed protein levels were in line with those previously reported for old and modern durum wheat varieties cropped under low N input management (Quaranta et al, 2010;De Vita et al, 2007b) and were also comparable with those obtained at higher nitrogen rates by Giuliani et al (2011). The protein accumulation was shown to be highly dependent on genotype, soil fertility (available N) and environmental conditions (temperature, water) (Giuliani et al, 2011;Dupont et al, 2006). In our study, the growing season was observed to have a big effect on protein content, with a significant increase from 143.5 to 161.4 g/kg during the second year compared to the previous one.…”
Section: Macronutrient Profilesupporting
confidence: 91%
“…All the varieties studied presented protein amounts that were higher than the minimum industry standard set at 125 g/kg (De Vita et al, 2007a). The observed protein levels were in line with those previously reported for old and modern durum wheat varieties cropped under low N input management (Quaranta et al, 2010;De Vita et al, 2007b) and were also comparable with those obtained at higher nitrogen rates by Giuliani et al (2011). The protein accumulation was shown to be highly dependent on genotype, soil fertility (available N) and environmental conditions (temperature, water) (Giuliani et al, 2011;Dupont et al, 2006).…”
Section: Macronutrient Profilesupporting
confidence: 90%
See 1 more Smart Citation
“…The observed protein content was in line with the values reported by Stagnari et al (2013), but it was lower with respect to our previous study which involved old and modern durum wheat varieties grown under low-input agricultural management (Dinelli et al, 2013). The main factors affecting protein accumulation are N availability and soil organic matter as well as climatic conditions (Giuliani et al, 2011) and their effects, which are particularly significant under organic and biodynamic management, which excludes the use of fertilizers throughout the crop cycle.…”
Section: Agronomic Traitssupporting
confidence: 86%
“…Previous research on wheat response to N fertilizer has focused mainly on bread wheat, and limited information is available regarding the effects of cultivar and N fertilizer rate on durum wheat NUE (López-Bellido et al, 2008;Giuliani et al, 2011b). Previous research on wheat response to N fertilizer has focused mainly on bread wheat, and limited information is available regarding the effects of cultivar and N fertilizer rate on durum wheat NUE (López-Bellido et al, 2008;Giuliani et al, 2011b).…”
Section: Cultivar and N Fertilizer Rate Affect Yield And N Use Efficimentioning
confidence: 99%